Possibility for Application of {99m}Tc-Methoxyisobutylisonitrile in Assessing the Efficiency of Chemotherapy Cardiotoxicity Prevention - Chernov V. I. Vladimir Ivanovich; Kravchuk T.; Zelchan R. V. Roman Vladimirovich; Podoplekin D.; Goldberg V. (Radiation Technologies in Medicine, 2015)
Title screen